PENGARUH PENDEKATAN PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN DAN KONEKSI MATEMATIS SISWA PADA MATERI PERBANDINGAN - Afifah, Fathin; Irawati, Riana; Maulana, M. (Jurnal Pena Ilmiah, 2017)
The purpose of this research was to improved understanding and connection mathematical ability by applying problem-based learning approached and conventional learning, the differents of improved about both of them, the connection between understanding ability and connection ability also students response after given the treatment used problem-based learning approached. Quasi-experiments method with control teams design wasn’t equivalent to used. The instrumen which used pretest and posttest questions, observation paper both teacher performance and students activity, also interview students guided. Based on the purpose of the research, the result student’s understanding and connection mathematical ability was improved, both at class experiment and control class. But, the result not refered that learning used by problem-based learning approached was better than conventional learning. A lot of factor which can make it happen. But, students responed was good after the class meeting used problem-based learning approached. Based on signification degree 0,05, the result showed that understanding and connection mathematical ability, both of them has positive connection.